2021
DOI: 10.1101/2021.09.27.21264091
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Population-scale analysis of common and rare genetic variation associated with hearing loss in adults

Abstract: Understanding the genetic underpinnings of disabling hearing loss, which affects ~466 million people worldwide, can provide avenues for new therapeutic target development. We performed a genome-wide association meta-analysis of hearing loss with 125,749 cases and 469,497 controls across five cohorts, including UK Biobank, Geisinger DiscovEHR, the Malmö Diet and Cancer Study, the Mount Sinai BioMe Personalized Medicine Cohort, and FinnGen. We identified 53 loci affecting hearing loss risk, 18 of which are novel… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 83 publications
0
7
0
Order By: Relevance
“…In the sex-combined GWAS meta-analysis including 501,825 individuals, we identified 54 LDindependent genome-wide significant associations, 14 of which are novel with respect to those identified by previous HL GWAS 8,13,16,54 . In the UKB-NHS-HPFS meta-analysis, three variants showed statistical differences between sexes in their effect size.…”
Section: Discussionmentioning
confidence: 72%
See 4 more Smart Citations
“…In the sex-combined GWAS meta-analysis including 501,825 individuals, we identified 54 LDindependent genome-wide significant associations, 14 of which are novel with respect to those identified by previous HL GWAS 8,13,16,54 . In the UKB-NHS-HPFS meta-analysis, three variants showed statistical differences between sexes in their effect size.…”
Section: Discussionmentioning
confidence: 72%
“…We identified that several genes previously implicated in HL pathogenesis because of their potential involvement in the peripheral structures of the auditory system, which also showed predicted expression differences in various brain regions. For example, while CRIP3 has broad expression in inner and outer hair cells 8 , we observed that transcriptomic changes of this gene in the putamen basal ganglia were associated with HL. Similarly, other genes that may be implicated in HL pathogenesis through both peripheral and central mechanisms include IPP (previously reported as highly expressed in human cochlear, cochlear hair cells, and spiral ganglion cells in mice 54 ), PIK3R3 (previously identified as specific to cell types in the cochlea 70 ), MAST2 (showing differential expression in the development of the inner ear 54 ), and SLC22A6 (identified as related to cochlear impairment 71 ).…”
Section: Discussionmentioning
confidence: 73%
See 3 more Smart Citations